Missouri v. Biden: Governmental Efforts to Suppress Free Expression - Russell L. Weaver (Public Governance, Administration and Finances Law Review, 2025)
The development of the internet, along with the creations of social media platforms, has created a unique opportunity for governmental officials to control freedom of expression. This article examines how the Biden Administration requested, encouraged, pressured and even threatened social media platforms to censor certain types of speech, and even to ban certain individuals from their platforms, and it analyses the Biden Administration’s actions in light of U.S. free speech principles.